The game night cookbook : snacks, noshes, and drinks for good times - Scott-Goodman, Barbara (The Countryman Press, An imprint of W. W. Norton & Company, Independent Publishers Since 1923, 2022)
"A playful cookbook for the next big game, poker night, or board game party. The Game Night Cookbook delivers smart methods for prepping and serving snacks, appetizers, small plates, sandwiches, desserts, and drinks that will please a crowd. Beyond just delicious recipes for Cacio e Pepe Popcorn, Gochujang Chicken Wings, Luscious Lemon Wafers, or a big batch of Peach & Strawberry Sangria, readers will find suggested menus perfect for lively get-togethers such as Competitive Party Game Nights, At-Home Theater Evenings, An Afternoon of Cards, and a Swanky Cocktail Party. Each menu will feature a day-by-day game plan for prepping food and setting up the bar, helping hosts entertain with ease, and making sure that he or she won't miss out on too much of the fun. With the popularity of board games on the rise and the film industry often releasing major movies direct to view from the comfort of home, this book celebrates inviting, intimate gatherings and emphasizes the importance of living and eating well in this era of non-ostentatious, casual entertaining"--